Study of interphase adsorption layers to develop milk products - Омельченко, Світлана Борисівна; Горальчук, Андрій Богданович (Eastern-European Journal of Enterprise Technologies, 2014)
The paper considers forming interphase adsorption layers in emulsions and foams using a surfactant mixture and milk proteins. The main objective of the study is to substantiate using the surfactant mixture and milk proteins, which define the dispersed system stability. The emulsion formation process at temperatures above the fat crystallization temperature was carried out by determining the boundary shear stress, formed interphase adsorption layers, which was performed in 4×3600 s (interphase adsorption layer formation time that has the largest value of the boundary shear stress at a temperature of 20±1°C. Behavioral mechanisms of surfactants and milk proteins on the interphase surface were substantiated in the paper in order to determine their rational concentrations. The presented method allows to define the layer strength of the system without surfactants and, with introducing the surfactant mixture, determine the rational composition of the surfactant mixture, which allows to vary the strength of interphase adsorption layers and as a result produce foam-emulsion systems with the high foaming ability, stability and ductility. Research results can be applied by food technologists, as well as technologists specialized pastry shops to create foam-emulsion systems such as creams, souffle, ice-cream, etc. We propose to use milk proteins and surfactant mixture to control the stability of dispersed systems such as foams and emulsions, as well as stable foam-emulsion systems.